A molecular phylogeny of Rissoidae (Caenogastropoda: Rissooidea) allows testing the diagnostic utility of morphological traits. Issue 1 (30th May 2016) - Criscione, Francesco; Ponder, Winston Frank; Köhler, Frank; Takano, Tsuyoshi; Kano, Yasunori
Abstract: The Rissooidea is an evolutionarily ancient and mega-diverse group of marine micro-gastropods that occur from intertidal to deep waters at all latitudes. Their current systematics is predominantly based on phenetic grounds and there has been no comprehensive molecular phylogeny. Based on sequences of mitochondrial and nuclear DNA from the most complete sampling of Rissoidae to date, this work represents the first treatment of the group performed through a phylogenetic approach. The main goals are to clarify the phylogenetic position of the Rissoidae, investigate the relationships within rissoid taxa and test the utility of some diagnostic morphological traits. Our phylogeny indicates that the Rissoidae are one of six distinct family-lineages within the superfamily Rissooidea (along with Barleeiidae, Emblandidae, Lironobidae, Rissoinidae and Zebinidae) whose recognition is supported by several synapomorphies. While most of the characters studied exhibit widespread convergence, some others prove useful in separating genera and broader taxonomic groups. The relationships among rissoid taxa challenge the current systematics, indicating the non-monophyly of some genera with purportedly trans-oceanic distribution and the need of taxonomic revision for some highly diverse genera. Our phylogeny suggests that the Rissoidae originated in shallow seas and independently radiated into bathyal waters at least twice.